Electrolyte material and battery using same

The novel electrolyte material with specific composition Li4-3a-cbAlaMbxCl4-x-y addresses the issues of hydrogen sulfide generation and low conductivity in sulfide solid electrolytes, providing safe and efficient lithium-ion batteries.

JP7624630B2Active Publication Date: 2025-01-31PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021501928
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-02-28
Filing Date
2020-02-14
Publication Date
2025-01-31
Estimated Expiration
2040-02-14

AI Technical Summary

Technical Problem

Existing electrolytes for lithium-ion batteries, particularly those using sulfide solid electrolytes, face challenges with hydrogen sulfide generation when exposed to the atmosphere and have lower lithium-ion conductivity.

Method used

A novel electrolyte material represented by the composition formula Li4-3a-cbAlaMbxCl4-x-y, where M is selected from MG, CA, or ZR, with specific ratios of a, b, x, and y, enhances lithium-ion conductivity and prevents hydrogen sulfide formation.

Benefits of technology

The new electrolyte material exhibits high lithium-ion conductivity and ensures safety by preventing hydrogen sulfide generation, enabling batteries with excellent charging and discharge characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007624630000004
    Figure 0007624630000004
  • Figure 0007624630000005
    Figure 0007624630000005
  • Figure 0007624630000006
    Figure 0007624630000006
Patent Text Reader

Abstract

The present disclosure provides an electrolyte material having high lithium ion conductivity. 4-3a-cb Al a M b F x Cl y Br 4-x-y where M is at least one selected from the group consisting of Mg, Ca, and Zr, c represents the valence of M, and is one of the following five formulae:
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an electrolyte material and a battery using the same. [Background technology]

[0002] Patent Document 1 discloses an all-solid-state battery using a sulfide solid electrolyte. Non-Patent Documents 1 and 2 disclose batteries using LiAlCl4. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2011-129312 A [Non-patent literature]

[0004] [Non-Patent Document 1] J.Electrochem.SOC. 35, 124, (1977) [Non-Patent Document 2] J.Electrochem.SOC.1509,139,(1992) Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present disclosure is to provide an electrolyte material having high lithium ion conductivity. [Means for solving the problem]

[0006] The electrolyte material of the present disclosure is a material represented by the following composition formula (1). Li 4-3a-cb Al a M b F x Cl y Br 4-x-y (1) Here, M is at least one selected from the group consisting of Mg, Ca, and Zr, c represents the valence of M, and the following five mathematical formulas: 0 < a < 1.33, 0 ≤ b < 2, 0 < x < 4, 0 ≤ y < 4, and (x + y) ≤ 4, are satisfied.

Effect of the Invention

[0007] The present disclosure provides an electrolyte material having high lithium ion conductivity.

Brief Description of the Drawings

[0008] [Figure 1] FIG. 1 shows a cross-sectional view of a battery 1000 according to the second embodiment. [Diagram 2] FIG. 2 shows a schematic diagram of a pressure molding die 300 used to evaluate the ionic conductivity of an electrolyte material. [Diagram 3] FIG. 3 is a graph of a Cole-Cole diagram showing the AC impedance measurement results of the electrolyte material according to Example 1. [Figure 4] FIG. 4 is a graph showing the initial discharge characteristics of the batteries according to Example 1 and Comparative Example 1.

Modes for Carrying Out the Invention

[0009] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings.

[0010] (First Embodiment) The electrolyte material according to the first embodiment is a material represented by the following compositional formula (1). Li 4-3a-cb Al a M b F x Cl y Br 4-x-y ···(1) Here, M is at least one selected from the group consisting of Mg, Ca, and Zr, c represents the valence of M, and the following five mathematical formulas: 0 < a < 1.33, 0 ≤ b < 2, 0 < x < 4, 0 ≤ y < 4, and (x + y) ≤ 4, are satisfied.

[0011] The electrolyte material according to the first embodiment has high lithium ion conductivity.

[0012] The electrolyte material according to the first embodiment can be used to obtain a battery with excellent charge and discharge characteristics. An example of such a battery is an all-solid-state secondary battery.

[0013] Since the electrolyte material according to the first embodiment does not contain sulfur, hydrogen sulfide is not generated even when exposed to the atmosphere. Therefore, the electrolyte material according to the first embodiment is excellent in safety. Note that hydrogen sulfide can be generated when the sulfide solid electrolyte disclosed in Patent Document 1 is exposed to the atmosphere.

[0014] In order to increase the ionic conductivity of the electrolyte material, in formula (1), 0.4 ≦ x ≦ 2.0 may be satisfied. In order to further increase the ionic conductivity, 0.8 ≦ x ≦ 1.8 may be satisfied.

[0015] In order to increase the ionic conductivity of the electrolyte material, in formula (1), 1 ≦ a ≦ 1.25 may be satisfied. In order to further increase the ionic conductivity, 1 ≦ a ≦ 1.2 may be satisfied. In order to increase the ionic conductivity of the electrolyte material, M may be Zr. In order to increase the ionic conductivity of the electrolyte material, b = 0 may be satisfied. That is, the electrolyte material may be a material represented by the following compositional formula (2). Li 4-3a Al a F x Cl y Br 4-x-y ···(2) Here, the following four mathematical formulas: 0 < a < 1.33, 0 < x < 4, 0 ≦ y < 4, and (x + y) ≦ 4 are satisfied.

[0016] The electrolyte material according to the first embodiment may be crystalline or amorphous.

[0017] The shape of the electrolyte material according to the first embodiment is not limited. Examples of the shape of the electrolyte material according to the first embodiment are needle-like, spherical, or elliptical. For example, the electrolyte material according to the first embodiment may be particles. The electrolyte material according to the first embodiment may be formed to have a pellet or plate shape.

[0018] For example, when the electrolyte material according to the first embodiment has a particulate (e.g., spherical) shape, the electrolyte material may have a median diameter of 0.1 μm or more and 100 μm or less. The electrolyte material according to the first embodiment may have a median diameter of 0.5 μm or more and 10 μm or less. This allows the electrolyte material to have higher ion conductivity. Furthermore, the electrolyte material can form a good dispersion state with other materials such as active materials.

[0019] <Method of manufacturing electrolyte material> The electrolyte material according to the first embodiment is produced, for example, by the following method.

[0020] The raw material powders of the halides are mixed to have a desired composition. As an example, the desired composition is LiAlF 1.6 Cl 2.4 In this case, LiCl, AlCl3, and AlF3 are mixed in a LiCl:AlCl3:AlF3 molar ratio of about 1.0:0.47:0.53. Alternatively, LiF, AlCl3, and AlF3 may be mixed in a LiF:AlCl3:AlF3 molar ratio of about 1.0:0.8:0.2. The raw material powders may be mixed in a molar ratio previously adjusted to offset composition changes that may occur during the synthesis process.

[0021] The raw material powders may be reacted with each other mechanochemically (i.e., using the method of mechanochemical milling) in a mixing device such as a planetary ball mill to obtain the reactants, or the mixture of raw material powders may be calcined in a vacuum or in an inert atmosphere (e.g., an argon atmosphere or a nitrogen atmosphere) to obtain the reactants.

[0022] By these methods, the electrolyte material according to the first embodiment is obtained.

[0023] Second embodiment A second embodiment of the present disclosure will be described below. The matters described in the first embodiment will be omitted as appropriate.

[0024] The battery according to the second embodiment includes a positive electrode, an electrolyte layer, and a negative electrode. The electrolyte layer is disposed between the positive electrode and the negative electrode.

[0025] At least one selected from the group consisting of the positive electrode, the electrolyte layer, and the negative electrode contains the electrolyte material according to the first embodiment.

[0026] The battery according to the second embodiment has excellent charge / discharge characteristics since it contains the electrolyte material according to the first embodiment.

[0027] FIG. 1 shows a cross-sectional view of a battery 1000 according to a second embodiment.

[0028] The battery 1000 according to the second embodiment includes a positive electrode 201, an electrolyte layer 202, and a negative electrode 203. The electrolyte layer 202 is disposed between the positive electrode 201 and the negative electrode 203.

[0029] The positive electrode 201 contains positive electrode active material particles 204 and electrolyte particles 100 .

[0030] The electrolyte layer 202 contains an electrolyte material (eg, a solid electrolyte material).

[0031] The negative electrode 203 contains negative electrode active material particles 205 and electrolyte particles 100 .

[0032] The electrolyte particle 100 is a particle made of the electrolyte material according to the first embodiment, or a particle containing the electrolyte material according to the first embodiment as a main component. A particle containing the electrolyte material according to the first embodiment as a main component means a particle in which the electrolyte material according to the first embodiment is contained in the largest amount.

[0033] The positive electrode 201 contains a material capable of absorbing and releasing metal ions (for example, lithium ions). The positive electrode 201 contains, for example, a positive electrode active material (for example, positive electrode active material particles 204).

[0034] Examples of the positive electrode active material include a lithium-containing transition metal oxide, a transition metal fluoride, a polyanion material, a fluorinated polyanion material, a transition metal sulfide, a transition metal oxyfluoride, a transition metal oxysulfide, or a transition metal oxynitride. An example of the lithium-containing transition metal oxide is Li(NiCoAl)O2 or LiCoO2.

[0035] The positive electrode active material particles 204 may have a median diameter of 0.1 μm or more and 100 μm or less. When the positive electrode active material particles 204 have a median diameter of 0.1 μm or more, the positive electrode active material particles 204 and the electrolyte particles 100 can be well dispersed in the positive electrode. This improves the charge / discharge characteristics of the battery. When the positive electrode active material particles 204 have a median diameter of 100 μm or less, the lithium diffusion rate in the positive electrode active material particles 204 improves. This allows the battery to operate at high power.

[0036] The positive electrode active material particles 204 may have a larger median diameter than the electrolyte particles 100. This allows the positive electrode active material particles 204 and the electrolyte particles 100 to be dispersed well.

[0037] From the viewpoint of the energy density and output of the battery, in the positive electrode 201, the ratio of the volume of the positive electrode active material particles 204 to the total volume of the positive electrode active material particles 204 and the electrolyte particles 100 may be 0.30 or more and 0.95 or less.

[0038] From the viewpoint of the energy density and output of the battery, the positive electrode 201 may have a thickness of 10 μm or more and 500 μm or less.

[0039] The electrolyte material contained in the electrolyte layer 202 may be the electrolyte material according to the first embodiment.

[0040] The electrolyte layer 202 may be a solid electrolyte layer.

[0041] The electrolyte layer 202 may be composed only of the electrolyte material according to the first embodiment.

[0042] The electrolyte layer 202 may be composed only of an electrolyte material (e.g., a solid electrolyte material) different from the electrolyte material according to the first embodiment. Examples of the electrolyte material different from the electrolyte material according to the first embodiment include Li2MgX4, Li2FeX4, Li(Ga,In)X4, Li3(Y,Gd,Sm,Al,Ga,In)X6, Li2ZrX6, or LiI, where X is at least one selected from the group consisting of F, Cl, Br, and I.

[0043] Hereinafter, the electrolyte material according to the first embodiment will be referred to as a first electrolyte material, and an electrolyte material different from the electrolyte material according to the first embodiment will be referred to as a second electrolyte material.

[0044] The electrolyte layer 202 may contain not only the first electrolyte material but also the second electrolyte material. In the electrolyte layer 202, the first electrolyte material and the second electrolyte material may be uniformly dispersed.

[0045] The layer made of the first electrolyte material and the layer made of the second electrolyte material may be stacked in the stacking direction of the battery 1000.

[0046] The electrolyte layer 202 may have a thickness of 1 μm or more and 100 μm or less. When the electrolyte layer 202 has a thickness of 1 μm or more, the positive electrode 201 and the negative electrode 203 are less likely to short-circuit. When the electrolyte layer 202 has a thickness of 100 μm or less, the battery can operate at high power.

[0047] The negative electrode 203 contains a material capable of absorbing and releasing metal ions (for example, lithium ions). The negative electrode 203 contains, for example, a negative electrode active material (for example, negative electrode active material particles 205).

[0048] Examples of the negative electrode active material are metal materials, carbon materials, oxides, nitrides, tin compounds, or silicides. The metal material may be a single metal or an alloy. Examples of the metal material are lithium metal or lithium alloys. Examples of the carbon material are natural graphite, coke, partially graphitized carbon, carbon fiber, spherical carbon, artificial graphite, or amorphous carbon. From the viewpoint of capacity density, suitable examples of the negative electrode active material are silicon (i.e., Si), tin (i.e., Sn), silicides, or tin compounds.

[0049] The negative electrode active material particles 205 may have a median diameter of 0.1 μm or more and 100 μm or less. When the negative electrode active material particles 205 have a median diameter of 0.1 μm or more, the negative electrode active material particles 205 and the electrolyte particles 100 can be well dispersed in the negative electrode 203. This improves the charge / discharge characteristics of the battery. When the negative electrode active material particles 205 have a median diameter of 100 μm or less, the lithium diffusion rate in the negative electrode active material particles 205 improves. This allows the battery to operate at high power.

[0050] The negative electrode active material particles 205 may have a larger median diameter than the electrolyte particles 100. This allows the negative electrode active material particles 205 and the electrolyte particles 100 to be dispersed well.

[0051] From the viewpoint of the energy density and output of the battery, in the negative electrode 203, the ratio of the volume of the negative electrode active material particles 205 to the total volume of the negative electrode active material particles 205 and the electrolyte particles 100 may be 0.30 or more and 0.95 or less.

[0052] From the viewpoint of the energy density and output of the battery, the negative electrode 203 may have a thickness of 10 μm or more and 500 μm or less.

[0053] At least one selected from the group consisting of the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a second electrolyte material (e.g., a solid electrolyte material) for the purpose of increasing ionic conductivity, chemical stability, and electrochemical stability.

[0054] The second electrolyte material may be a sulfide solid electrolyte.

[0055] Examples of sulfide solid electrolytes are Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li 3.25 Ge 0.25 P 0.75 S4, or Li 10 GeP2S 12 It is.

[0056] The second electrolyte material may be an oxide solid electrolyte.

[0057] Examples of oxide solid electrolytes include: (i) NASICON-type solid electrolytes such as LiTi2(PO4)3 or elemental substitutions thereof; (ii) Perovskite-type solid electrolytes such as (LaLi)TiO3; (iii) Li 14 ZnGeO 16 LISICON-type solid electrolytes such as Li4SiO4, LiGeO4 or elemental substitutes thereof; (iv) Li7La3Zr2O 12 or a garnet-type solid electrolyte such as an elemental substitution product thereof; or (v) Li3PO4 or its N-substituted derivatives, It is.

[0058] The second electrolyte material may be a halide solid electrolyte, as described above.

[0059] Examples of halide solid electrolytes are Li2MgX4, Li2FeX4, Li(Ga,In)X4, Li3(Y,Gd,Sm,Al,Ga,In)X6, Li2ZrX6, or LiI, where X is at least one selected from the group consisting of F, Cl, Br, and I.

[0060] Other examples of halide solid electrolytes are Li p Me q Y rX'6, where p+mq+3r=6 and c>0 are satisfied. Me is at least one selected from the group consisting of metal elements and metalloid elements other than Li and Y. m represents the valence of Me. "Metalloid elements" are B, Si, Ge, As, Sb, and Te. "Metal elements" are all elements included in Groups 1 to 12 of the periodic table (excluding hydrogen) and all elements included in Groups 13 to 16 of the periodic table (excluding B, Si, Ge, As, Sb, Te, C, N, P, O, S, and Se).

[0061] From the viewpoint of ionic conductivity, Me may be at least one selected from the group consisting of Mg, Ca, Sr, Ba, Zn, Sc, Al, Ga, Bi, Zr, Hf, Ti, Sn, Ta, and Nb. The halide solid electrolyte may be, for example, Li3YCl6 or Li3YBr6.

[0062] The second electrolyte material may be an organic polymer solid electrolyte.

[0063] Examples of organic polymer solid electrolytes include a polymer compound and a lithium salt compound. The polymer compound may have an ethylene oxide structure. The polymer compound having an ethylene oxide structure can contain a large amount of lithium salt, and therefore can further increase the ionic conductivity.

[0064] Examples of the lithium salt are LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), or LiC(SO2CF3)3. As the lithium salt, the electrolyte material according to the first embodiment may be used. One type of lithium salt selected from the exemplified lithium salts may be used alone. Alternatively, a mixture of two or more types of lithium salts selected from the exemplified lithium salts may be used.

[0065] At least one selected from the group consisting of the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a nonaqueous electrolyte solution, a gel electrolyte, or an ionic liquid for the purpose of facilitating the exchange of lithium ions and improving the output characteristics of the battery.

[0066] The non-aqueous electrolyte contains a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent. Examples of non-aqueous solvents are cyclic carbonate solvents, chain carbonate solvents, cyclic ether solvents, chain ether solvents, cyclic ester solvents, chain ester solvents, or fluorine solvents. Examples of cyclic carbonate solvents are ethylene carbonate, propylene carbonate, or butylene carbonate. Examples of chain carbonate solvents are dimethyl carbonate, ethyl methyl carbonate, or diethyl carbonate. Examples of cyclic ether solvents are tetrahydrofuran, 1,4-dioxane, or 1,3-dioxolane. Examples of chain ether solvents are 1,2-dimethoxyethane or 1,2-diethoxyethane. Examples of cyclic ester solvents are γ-butyrolactone. Examples of chain ester solvents are methyl acetate. Examples of fluorine solvents are fluoroethylene carbonate, methyl fluoropropionate, fluorobenzene, fluoroethyl methyl carbonate, or fluorodimethylene carbonate. One type of non-aqueous solvent selected from these may be used alone, or a combination of two or more types of non-aqueous solvents selected from these may be used.

[0067] Examples of the lithium salt are LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), or LiC(SO2CF3)3. As the lithium salt, the electrolyte material according to the first embodiment may be used. One type of lithium salt selected from the exemplified lithium salts may be used alone. Alternatively, a mixture of two or more types of lithium salts selected from the exemplified lithium salts may be used. The concentration of the lithium salt is, for example, 0.5 mol / liter or more and 2 mol / liter or less.

[0068] In the battery according to the second embodiment, the electrolyte layer 202 may contain a nonaqueous electrolyte solution containing the electrolyte material according to the first embodiment. That is, the nonaqueous electrolyte solution contained in the electrolyte layer 202 may contain a nonaqueous solvent and the electrolyte material according to the first embodiment dissolved in the nonaqueous solvent. Such a battery has high oxidation resistance.

[0069] The gel electrolyte may be a polymer material impregnated with a non-aqueous electrolyte, such as polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, or a polymer having an ethylene oxide bond.

[0070] Examples of cations contained in ionic liquids are: (i) Aliphatic chain quaternary salts such as tetraalkylammonium or tetraalkylphosphonium salts, (ii) aliphatic cyclic ammonium such as pyrrolidiniums, morpholiniums, imidazoliniums, tetrahydropyrimidiniums, piperaziniums, or piperidiniums, or (iii) nitrogen-containing heterocyclic aromatic cations such as pyridiniums or imidazoliums; It is.

[0071] An example of an anion contained in an ionic liquid is PF6 - , BF4 - , SbF 6- - , AsF6 - , SO3CF3 - , N(SO2CF3)2 - , N(SO2C2F5)2 - , N(SO2CF3)(SO2C4F9) - , or C(SO2CF3)3 - It is.

[0072] The ionic liquid may contain a lithium salt. As the lithium salt, the electrolyte material according to the first embodiment may be used.

[0073] At least one selected from the group consisting of the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a binder for the purpose of improving adhesion between particles.

[0074] Examples of the binder are polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamideimide, polyacrylonitrile, polyacrylic acid, polyacrylic acid methyl ester, polyacrylic acid ethyl ester, polyacrylic acid hexyl ester, polymethacrylic acid, polymethacrylic acid methyl ester, polymethacrylic acid ethyl ester, polymethacrylic acid hexyl ester, polyvinyl acetate, polyvinylpyrrolidone, polyether, polyethersulfone, hexafluoropolypropylene, styrene butadiene rubber, or carboxymethylcellulose. Copolymers may also be used as binders. Examples of such binders are copolymers of two or more materials selected from the group consisting of tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, chlorotrifluoroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid, and hexadiene. A mixture of two or more materials selected from these may be used.

[0075] At least one selected from the positive electrode 201 and the negative electrode 203 may contain a conductive assistant for the purpose of increasing electronic conductivity.

[0076] Examples of the conductive additive include: (i) Graphites, such as natural or synthetic graphite; (ii) Carbon blacks such as acetylene black or ketjen black; (iii) conductive fibers, such as carbon or metal fibers; (iv) fluorocarbons, (v) Metal powders such as aluminum; (vi) conductive whiskers such as zinc oxide or potassium titanate; (vii) a conductive metal oxide, such as titanium dioxide; or (viii) conductive polymer compounds such as polyaniline, polypyrrole or polythiophene; In order to reduce costs, the above-mentioned conductive assistant (i) or (ii) may be used.

[0077] Examples of the shape of the battery according to the second embodiment are a coin type, a cylindrical type, a square type, a sheet type, a button type, a flat type, or a laminate type.

[0078] (Example) Hereinafter, the present disclosure will be described in more detail with reference to examples and comparative examples.

[0079] Example 1 [Preparation of electrolyte materials] In an argon atmosphere having a dew point of -60°C or less (hereinafter referred to as "dry argon atmosphere"), raw material powders of LiCl, AlCl3, and AlF3 were prepared so as to have a LiCl:AlCl3:AlF3 molar ratio of 1.0:0.87:0.13. These raw material powders were ground and mixed in a mortar. The resulting mixture was milled at 500 rpm for 15 hours using a planetary ball mill. In this manner, a powder of the electrolyte material according to Example 1 was obtained. The electrolyte material according to Example 1 was LiAlF 0.4 Cl 3.6 The composition was represented by the formula:

[0080] The contents of Li, Al, F, and Cl per unit weight in the entire electrolyte material according to Example 1 were measured. The contents of Li and Al were measured by inductively coupled plasma atomic emission spectrometry (ICP-AES). The contents of F and Cl were measured by ion chromatography. Based on the obtained contents of Li, Al, F, and Cl, the Li:Al:F:Cl molar ratio was calculated. As a result, the electrolyte material according to Example 1 had a Li:Al:F:Cl molar ratio of 1.0:1.0:0.4:3.6.

[0081] [Evaluation of ionic conductivity] FIG. 2 shows a schematic diagram of a pressing die 300 used to evaluate the ionic conductivity of the electrolyte material.

[0082] The pressure molding die 300 had a frame 301, a lower punch 302, and an upper punch 303. The frame 301 was made of insulating polycarbonate. The lower punch 302 and the upper punch 303 were both made of electronically conductive stainless steel.

[0083] Using the pressure molding die 300 shown in FIG. 3, the ionic conductivity of the electrolyte material according to Example 1 was measured by the following method.

[0084] In a dry argon atmosphere, the powder 101 of the electrolyte material according to Example 1 was filled into the inside of a pressing die 300. A pressure of 400 MPa was applied to the electrolyte material according to Example 1 using a lower punch 302 and an upper punch 303.

[0085] While the pressure was still applied, the lower punch 302 and the upper punch 303 were connected to a potentiostat (Princeton Applied Research, VersaSTAT4) equipped with a frequency response analyzer. The upper punch 303 was connected to a working electrode and a terminal for measuring potential. The lower punch 302 was connected to a counter electrode and a reference electrode. The impedance of the electrolyte material according to Example 1 was measured by an electrochemical impedance measurement method at room temperature.

[0086] FIG. 3 is a graph of a Cole-Cole diagram showing the AC impedance measurement results of the electrolyte material according to Example 1.

[0087] In FIG. 3, the real value of the impedance at the measurement point where the absolute value of the phase of the complex impedance is the smallest was considered to be the resistance value to the ion conduction of the electrolyte material. The real value is indicated by the arrow R SEUsing the resistance value, the ionic conductivity was calculated based on the following formula (2). σ = (R SE ×S / t) -1 (2) Here, σ represents ion conductivity. S represents the contact area of ​​the electrolyte material with the punch upper portion 303 (equal to the cross-sectional area of ​​the hollow portion of the frame mold 301 in FIG. 2). R SE represents the resistance value of the electrolyte material in the impedance measurement, and t represents the thickness of the electrolyte material (i.e., the thickness of the layer formed from the powder 101 of the electrolyte material in FIG. 2).

[0088] The ionic conductivity of the electrolyte material according to Example 1 measured at 25° C. is 2.5×10 -5 It was S / cm.

[0089] [Battery construction] In a dry argon atmosphere, the electrolyte material according to Example 1 and the positive electrode active material LiCoO2 were prepared in a volume ratio of about 50:50. These materials were mixed in an agate mortar. In this way, a mixture was obtained.

[0090] In an insulating cylinder having an inner diameter of 9.5 mm, the electrolyte material according to Example 1, the above mixture (9.6 mg), and aluminum powder (14.7 mg) were laminated in this order. A pressure of 300 MPa was applied to this laminate to form a solid electrolyte layer and a first electrode. The solid electrolyte layer had a thickness of 700 μm.

[0091] Next, metal In (thickness 200 μm) was laminated on the solid electrolyte layer. A pressure of 80 MPa was applied to this laminate to form a second electrode. The first electrode was a positive electrode, and the second electrode was a negative electrode.

[0092] Next, current collectors made of stainless steel were attached to the first and second electrodes, and current collecting leads were attached to the current collectors.

[0093] Finally, the inside of the insulating cylinder was isolated from the outside atmosphere by using an insulating ferrule, and the inside of the cylinder was sealed. In this manner, the battery according to Example 1 was obtained.

[0094] [Charge / discharge test] 4 is a graph showing the initial discharge characteristics of the battery according to Example 1. The initial charge / discharge characteristics were measured by the following method.

[0095] The battery according to Example 1 was placed in a thermostatic chamber at 25°C.

[0096] The battery according to Example 1 was charged at a current value resulting in a 0.05C rate until a voltage of 3.6V was reached.

[0097] Next, the battery according to Example 1 was discharged at a current value that was also 0.05C rate until a voltage of 1.9V was reached.

[0098] As a result of the charge / discharge test, the battery according to Example 1 had an initial discharge capacity of 290 μAh.

[0099] (Examples 2 to 32) In Examples 2 to 24, LiCl, AlCl3, and AlF3 were prepared as raw material powders so as to have a LiCl:AlCl3:AlF3 molar ratio of (4-3a):(ax / 3):x / 3.

[0100] In Examples 25 to 29, LiBr, AlBr3, and AlF3 were prepared as raw material powders so as to have a LiBr:AlBr3:AlF3 molar ratio of (4-3a):(ax / 3):x / 3.

[0101] In Examples 30 to 32, LiCl, AlCl3, AlBr3, and AlF3 were prepared as raw material powders in a LiCl:AlCl3:AlBr3:AlF3 molar ratio of (4-3a):{a+(y-4) / 3}:(4-xy) / 3:x / 3.

[0102] In Examples 4, 6, 8, 15, 16, 18, 20, and 23, the mixture of raw material powders was milled using a planetary ball mill and then heat-treated at 150° C. for 30 minutes in a dry argon atmosphere.

[0103] Except for the above, the electrolyte materials according to Examples 2 to 32 were obtained in the same manner as in Example 1.

[0104] For the electrolyte materials according to Examples 2-32, the values ​​of a, b, x, and y are shown in Table 1.

[0105] The ionic conductivity of the electrolyte materials according to Examples 2 to 32 was measured in the same manner as in Example 1. The measurement results are shown in Table 1.

[0106] Using the electrolyte materials according to Examples 2 to 32, batteries according to Examples 2 to 32 were obtained in the same manner as in Example 1. Using the batteries according to Examples 2 to 32, charge / discharge tests were performed in the same manner as in Example 1. As a result, the batteries according to Examples 2 to 32 were successfully charged and discharged in the same manner as in Example 1.

[0107] (Examples 33 to 50) In Examples 33 to 40, LiCl, AlCl3, MgCl2, and AlF3 were prepared as raw material powders so as to have a LiCl:AlCl3:MgCl2:AlF3 molar ratio of (4-3a-cb):(ax / 3):b:x / 3.

[0108] In Examples 41 to 46, LiCl, AlCl3, CaCl2, and AlF3 were prepared as raw material powders so as to have a LiCl:AlCl3:CaCl2:AlF3 molar ratio of (4-3a-cb):(ax / 3):b:x / 3.

[0109] In Examples 47 to 50, LiCl, AlCl3, ZrCl4, and AlF3 were prepared as raw material powders so as to have a LiCl:AlCl3:ZrCl4:AlF3 molar ratio of (4-3a-cb):(ax / 3):b:x / 3.

[0110] Except for the above, the electrolyte materials according to Examples 33 to 50 were obtained in the same manner as in Example 1.

[0111] For the electrolyte materials according to Examples 33-50, the values ​​of a, b, c, x, and y are shown in Table 2.

[0112] The ionic conductivity of the electrolyte materials according to Examples 33 to 50 was measured in the same manner as in Example 1. The measurement results are shown in Table 2.

[0113] (Comparative Examples 1 to 3) In Comparative Example 1, LiCl and AlCl3 were prepared as raw material powders so that the LiCl:AlCl3 molar ratio was 1:1.

[0114] In Comparative Example 2, LiBr and AlBr3 were prepared as raw material powders so that the LiBr:AlBr3 molar ratio was 1:1.

[0115] In Comparative Example 3, LiF and AlF3 were prepared as raw material powders so that the LiF:AlF3 molar ratio was 1:1.

[0116] Except for the above, the electrolyte materials according to Comparative Examples 1 to 3 were obtained in the same manner as in Example 1.

[0117] For the electrolyte materials according to Comparative Examples 1 to 3, the values ​​of a, b, x, and y are shown in Table 3.

[0118] The ionic conductivity of the electrolyte materials according to Comparative Examples 1 to 3 was measured in the same manner as in Example 1. The measurement results are shown in Table 3.

[0119] Using the electrolyte materials according to Comparative Examples 1 to 3, batteries according to Comparative Examples 1 to 3 were obtained in the same manner as in Example 1. Using the batteries according to Comparative Examples 1 to 3, charge / discharge tests were performed in the same manner as in Example 1. As a result, the batteries according to Comparative Examples 1 to 3 had an initial discharge capacity of 1 μAh or less. The batteries according to Comparative Examples 1 to 3 were neither charged nor discharged.

[0120] [Table 1]

[0121] [Table 2]

[0122] [Table 3]

[0123] (Consideration) As is clear from Tables 1 and 2, the electrolyte materials according to Examples 1 to 50 had a melting point of 1×10 -5 On the other hand, as is clear from Table 3, the electrolyte materials according to Comparative Examples 1 to 3 have a high ionic conductivity of 1×10 -5 It has an ionic conductivity of less than S / cm.

[0124] In general, when a part of chlorine or bromine is replaced with fluorine in an electrolyte material, the electrochemical stability is improved, but the ionic conductivity is reduced. This is because fluorine has a very large electronegativity, so fluorine tends to strongly attract cations and inhibit the conduction of lithium ions. However, in the electrolyte material of the present disclosure, the ionic conductivity is improved by introducing fluorine.

[0125] As is apparent from Tables 1 and 2, when 0.4≦x≦2.0 is satisfied in formula (1), the electrolyte material has high ionic conductivity. As is apparent from a comparison of Examples 2 to 12 with Example 1, when 0.8≦x≦1.8 is satisfied, the ionic conductivity is further increased.

[0126] As is clear from Table 2, even when M is at least one selected from the group consisting of Mg, Ca, and Zr (i.e., 0 < b < 2 is satisfied in Formula (1)), the electrolyte material had high ionic conductivity.

[0127] As is clear from Examples 47 to 50, when M is Zr, the electrolyte material has a high ionic conductivity of 1×10 -4 S / cm or more.

[0128] As is clear from Table 1 and Table 2, when 1.0 ≤ a ≤ 1.25 is satisfied in Formula (1), the electrolyte material has high ionic conductivity.

[0129] The batteries according to Examples 1 to 32 were all charged and discharged at room temperature. On the other hand, the batteries according to Comparative Examples 1 to 3 were neither charged nor discharged. Furthermore, since the electrolyte materials according to Examples 1 to 32 do not contain sulfur, hydrogen sulfide is not generated.

[0130] As described above, the electrolyte material according to the present disclosure is a material that does not generate hydrogen sulfide and has high lithium ion conductivity. The electrolyte material according to the present disclosure is suitable for providing a battery that can be charged and discharged well.

Industrial Applicability

[0131] The electrolyte material of the present disclosure is used, for example, in all-solid-state lithium ion secondary batteries.

Explanation of Signs

[0132] 100 Electrolyte particles 101 Powder of electrolyte material 201 Positive electrode 202 Electrolyte layer 203 Negative electrode 204 Positive electrode active material particles 205 Negative electrode active material particles 300 Pressing die 301 Frame type 302 Lower punch 303 Punch top 1000 batteries

Claims

1. An electrolyte material represented by the following composition formula (1): Li 4-3a-cb Al a M b F x Cl y Br 4-x-y ・・・(1) Here, M is at least one selected from the group consisting of Mg, Ca, and Zr, c represents the valence of M, and The following five formulas: 0<a<1.33, 0≦b≦0.31, 0<x<4, 0≦y<4, When b=0, (x+y)≦4, and When b≠0, (x+y)=4 is satisfied, The electrolyte material has a powder, particle, or pellet shape. Electrolyte materials.

2. 0.4≦x≦2.0 is satisfied; The electrolyte material according to claim 1 .

3. 0.8≦x≦1.8 is satisfied; The electrolyte material according to claim 2 .

4. 1≦a≦1.25 is satisfied; The electrolyte material according to claim 1 .

5. 1≦a≦1.2 is satisfied; The electrolyte material according to claim 4 .

6. A positive electrode and A negative electrode; an electrolyte layer disposed between the positive electrode and the negative electrode; Equipped with At least one selected from the group consisting of the positive electrode, the negative electrode, and the electrolyte layer contains the electrolyte material according to any one of claims 1 to 5. battery.

7. The electrolyte layer contains a nonaqueous electrolyte solution and the electrolyte material according to any one of claims 1 to 5.

7. The battery of claim 6.

Citation Information

Patent Citations

  • Electrolyte for electrochemical cell and electrochemical cell containing same electrolyte

    JP1981038775A

  • rechargeable electrochemical battery

    JP2003502830A

  • Method of manufacturing sulfide solid electrolyte material, sulfide solid electrolyte material, and lithium battery

    JP2011129312A

  • Solid electrolyte, method for producing the same, and battery

    JP2017139142A

  • Solid electrolyte, battery electronic equipment and movable body

    JP2018037325A